Moral disengagement, normative beliefs of peer group and attitudes regarding roles in bullying. - Almeida, A. (2010)
This article examines how moral disengagement, empathy, belief in a just world, and peer group normative beliefs regarding the roles of bully and defender of the victim are associated with attitudes regarding the roles of the bully and the defender of the victim. Two hundred ninety-two students from grades 6–9 participated. Results showed that more positive attitudes regarding role of bully were predicted by higher levels of moral disengagement, whereas more positive attitudes regarding the role of defender of the victim were predicted by lower levels of moral disengagement. The perception of the normative beliefs of the peer group also predicted the attitudes of participants regarding the respective role.